Continuous synthesis of tetraalkylammonium‐Based ethyl sulphate ionic liquid and its kinetic study in microreactors. Issue 4 (12th January 2019) - Zhang, Hong; Shang, Minjing; Song, Yang; Su, Yuanhai
Abstract : A tetraalkylammonium‐based ionic liquid (IL) was synthesized with diethyl sulphate and triethylamine in a capillary microreactor. Solvent‐free conditions coupled with microreactor technology greatly simplified the IL construction process. Optimization of process parameters (e.g., temperature, residence time, and inner diameter of capillary) was performed, and the maximum yield was 94% with the residence time of 300 s at 90°C. Interestingly, the obtained product could exist as a molten salt with low viscosity at a low melting point of 24.1°C. Key dimensionless groups such as Pe, Bo, and DaII numbers were calculated to account for the mass transport phenomena and reaction performance in this IL synthesis or to validate the reliability of the corresponding reaction kinetics study. Based on fast heat and mass transfer rates provided by the microreactor, intrinsic reaction kinetics could be obtained. Moreover, gold (III) extraction was remarkably improved by the application of the synthesized IL. © 2018 American Institute of Chemical Engineers AIChE J, 65: 1245–1255, 2019